2019
DOI: 10.3892/or.2019.7028
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and analysis of circRNA‑miRNA‑mRNA network in the pathology of cervical cancer

Abstract: The present study was performed with the aim of understanding the mechanisms of pathogenesis and providing novel biomarkers for cervical cancer by constructing a regulatory circular (circ)RNA-micro (mi)RNA-mRNA network. Using an adjusted P-value of <0.05 and an absolute log value of fold-change >1, 16 and 156 miRNAs from GSE30656 and The Cancer Genome Atlas (TCGA), 5,321 mRNAs from GSE63514, 4,076 mRNAs from cervical squamous cell carcinoma and endocervical adenocarcinoma (from TCGA) and 75 circRNAs from GSE10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 88 publications
(80 reference statements)
2
60
0
Order By: Relevance
“…Our results indicated that RRM2 is upregulated and significantly associated with poor prognosis in cervical cancer, and these results are in line with previous studies [18,19,36,40]. With 192 samples (29 normal, 30 low-grade dysplasia, 30 high-grade dysplasia and 103 invasive cancer tissue specimens) and SiHa cervical cancer cells, Su et al reported the expression of RRM2 in cancer tissues was increased when compared to high-grade dysplasia, low-grade dysplasia or normal cervical tissues [40].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results indicated that RRM2 is upregulated and significantly associated with poor prognosis in cervical cancer, and these results are in line with previous studies [18,19,36,40]. With 192 samples (29 normal, 30 low-grade dysplasia, 30 high-grade dysplasia and 103 invasive cancer tissue specimens) and SiHa cervical cancer cells, Su et al reported the expression of RRM2 in cancer tissues was increased when compared to high-grade dysplasia, low-grade dysplasia or normal cervical tissues [40].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our previous research has also shown that higher expression of RRM2 is associated with a significantly poorer overall survival [18]. However, relatively little is known about the role of RRM2 in cervical cancer and even less is known of the mechanisms responsible for its effects.…”
Section: Ivyspringmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have shown that circRNAs can exert as a sponge on miRNAs to regulate the expression of downstream target genes of miRNAs and affect tumor occurrence and development. [18][19][20] MiR-155 is an important member of the microRNAs family, and due to its versatile nature, miR-155 has attracted extensive attention and extensive research. A large number of studies have shown that miR-155 has a wide range of functions, involving many biological processes such as developmental differentiation of hematopoietic cells, developmental differentiation of immune cells, inflammatory response, immune response, muscle development, and fat differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…DEcircRNAs with the target miRNAs. To obtain high-quality circRNAs acting as miRNA targets and distinguish those circRNAs acting as miRNA decoys, the circRNAs that had perfect nucleotide pairing between the 2nd and 8th positions of the 5' end of miRNA sequences were selected [17]. The miRNAs within circRNA-miRNA interactions were further screened by DEmiRNAs identi ed from TCGA.…”
Section: Data Processingmentioning
confidence: 99%